Roles of Mn and Ni in Li-rich Mn-Ni-Fe oxide cathodes. (March 2021) - Aryal, Shankar; Kucuk, Kamil; Timofeeva, Elena V.; Segre, Carlo U.
Graphical abstract: Highlights: Structure formation of Li-rich Mn, Ni and Fe oxides with composition is studied. Composite oxides showed superior capacity and voltage stability. Ni 2+ fraction is directly related to Li + /Ni 2+ mixing and voltage fading. Mn reduced upon cycling but the reduction is independent of Mn fraction in Li-rich Mn-Ni-Fe oxide series. Mn reduction has less severe effect on voltage fading than Li + /Ni 2+ mixing. Abstract: Cobalt free, lithium-rich manganese, nickel, and iron composite oxides (nanoscale mixture of monoclinic, Li2 MnO3, and rhombohedral, LiMO2, phases) are promising cathodes as they show attractive electrochemical performance in initial cycles and can reduce the cost and toxicity of lithium ion battery. However, capacity and voltage fading on cycling are the downsides. To better understand the electrochemical performance and degradation mechanism, a series of Li1.2 Mn0.40+x Ni0.30-x Fe0.10 O2 materials with x = 0, 0.05, 0.10, and 0.15 was synthesized and systematically studied. The results of this study suggest that two phase composition is beneficial for superior electrochemical performance. The series showed first discharge capacity at 0.1C of 267, 204, 226, and 277 mAhg −1 for x = 0, 0.05, 0.10, and 0.15 respectively, with capacity retention after 100 cycles at 0.3C of 57 %, 57 %, 94 % and 67 %. For the first time we report EXAFS data analysis at all three K-edges: Mn, Ni and Fe before and after extended cycling. Ni reduction to Ni 2+ after cycling and voltage fading increased with Ni fraction in the series. There is no trend of Mn reduction (Li2 MnO3 activation) on cycling with Mn content indicating composition selection is crucially important for improved performance. The information on changes in electronic states and atomic distances, which allows proposing comprehensive electrochemical (role of Li2 MnO3 phase) and degradation (Li + /Ni 2+ exchange, voltage fading, and capacity fading) mechanisms.